Body composition of women 20–49 years old as a predictor for noncommunicable diseases: a community-based study. Issue 1 (March 2016) - Rizk, Hoda I.I.; Kamal Elden, Nesreen M.
Abstract : Background: Obesity increases a person's risk of developing a number of noncommunicable diseases (NCDs), including, type 2 diabetes, coronary heart disease, hypertension, and certain cancers. The bioelectrical impedance analysis (BIA) has been considered as a safe, noninvasive, simple, and least expensive portable method for the evaluation of body composition in clinical practice. However, there is not enough information about its use in community-based surveys to detect the optimal cutoff point for the body fat percent (BF%) that could predict NCDs. Objective: To identify the cutoff point for the BF%, at which NCD risk could be predicted compared with BMI and waist circumference (WC). Methods: A community-based study was conducted in a randomly selected cluster located within the catchment area of Cairo University Hospitals. All ever-married women 20–49 years old and not currently pregnant ( n =373) in the selected cluster were included in the study. A questionnaire was used for recoding data during the household survey. Portable equipment that estimates body composition (water, fat, protein, and bone) through BIA was used. Results: Receiver operating characteristic curve analysis showed cutoff point for BF% of 37.5% ( P =0.02) at the time of reporting hypertension, with 78% sensitivity and 40% specificity. For diagnosed diabetes, cutoff point for the BF% was 38.5% ( P =0.005), with 71% sensitivity and 46% specificity. For diagnosed cardiovascular diseases, cutoff point for BF% was 38.5% ( P =0.001) with 86% sensitivity and 47% specificity. For diagnosed joint diseases, cutoff point for BF% was 38.5% ( P =0.005), with 67% sensitivity and 48% specificity. Conclusion and recommendations: BIA was effective in predicting and suggesting the cutoff points for the BF% associated with four types of NCDs (hypertension, cardiovascular, diabetes, and joint diseases). The use of BIA for women before the age of 20 years could guide strategies for reducing body fat and its risk of NCDs.